Notable American women, 1607-1950 a biographical dictionary - James, Edward T.; James, Janet Wilson 1918-; Boyer, Paul S. (Belknap Press of Harvard University Press, 1971)
Contains biographical sketches of women whose achievements have contributed to the nation's history.